Assessing Risk of Storm Surge for Coastal Provinces in Viet Nam. Issue 2 (14th March 2022) - Hien, Nguyen Xuan; Tra, Tran Van; Thanh, Nguyen Thi; Nguyen, Hong Hanh; Le, Duc Quyen; Pham, Van Sy
Abstract: Viet Nam is seriously affected by natural disasters including storms and storm surges. Assessing disaster risks, particularly storm surges for coastal provinces, thus, provides not only scientific evidence but also supports policymaking in natural disaster prevention and control. Given this importance, this study assesses the risks of storm surges in Vietnamese coastal provinces. The results show that the coastal areas of Quang Ninh, Thanh Hoa, Nghe An, Ha Tinh, Quang Tri and Hue face the highest risk of storm surges. On the contrary, other provinces including Da Nang, Quang Nam, Binh Dinh, Phu Yen, and Ba Ria- Vung Tau face the lowest risk of storm surges. The results provide useful information for better natural disaster preparedness in Viet Nam, namely planning and zoning of future development as well as supporting early warning efforts.